2018
DOI: 10.1136/tsaco-2018-000219
|View full text |Cite
|
Sign up to set email alerts
|

Early and late complications of bariatric operation

Abstract: Weight loss surgery is one of the fastest growing segments of the surgical discipline. As with all medical procedures, postoperative complications will occur. Acute care surgeons need to be familiar with the common problems and their management. Although general surgical principles generally apply, diagnoses specific to the various bariatric operations must be considered. There are anatomic considerations which alter management priorities and options for these patients in many instances. These problems present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
102
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(112 citation statements)
references
References 59 publications
3
102
1
6
Order By: Relevance
“…They were carried out in a lower body mass index (BMI 27.5 kg/m 2 ) for Chinese people owing to racial difference. However, some side effects have been reported, such as anemia, infections, gallstones, and dyspnea [2]. Subsequently, several studies found that bone mineral density (BMD) was obviously affected after gastric surgery, especially at the femoral neck (FN) and total hip (TH) [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They were carried out in a lower body mass index (BMI 27.5 kg/m 2 ) for Chinese people owing to racial difference. However, some side effects have been reported, such as anemia, infections, gallstones, and dyspnea [2]. Subsequently, several studies found that bone mineral density (BMD) was obviously affected after gastric surgery, especially at the femoral neck (FN) and total hip (TH) [2].…”
mentioning
confidence: 99%
“…However, some side effects have been reported, such as anemia, infections, gallstones, and dyspnea [2]. Subsequently, several studies found that bone mineral density (BMD) was obviously affected after gastric surgery, especially at the femoral neck (FN) and total hip (TH) [2]. It becomes an urgent problem to be resolved and draws our attention [3].…”
mentioning
confidence: 99%
“…These include appetite suppressants and blockade of fat absorption (4), but are frequently accompanied by unacceptable side effects or eventual lack of efficacy. More recently, invasive procedures such as bariatric surgery have also been prescribed (4), and while to date this approach has proven effective at ameliorating insulin resistance and providing sustained weight loss, the risks associated with such radical surgeries are not to be underestimated (5). On the other hand, one potential means to increase energy expenditure aside from physical exercise is energyconsuming futile metabolic cycles and uncoupled respiration (6).…”
Section: Introductionmentioning
confidence: 99%
“…Australian and International guidelines recommend bariatric surgery should only be offered in high-volume, specialized units with adequate allied-health support and follow-up capability [2,3]. This is required to prevent late weight regain and avoidable complications such as nutritional deficiencies [4,5]. Increased patient geographical distances from bariatric units are associated with poorer follow-up and potentially poorer outcomes [6][7][8].…”
Section: Introductionmentioning
confidence: 99%